2015
DOI: 10.1103/physrevlett.114.055503
|View full text |Cite
|
Sign up to set email alerts
|

Origami Multistability: From Single Vertices to Metasheets

Abstract: We show that the simplest building blocks of origami-based materials-rigid, degree-four vertices-are generically multistable. The existence of two distinct branches of folding motion emerging from the flat state suggests at least bistability, but we show how nonlinearities in the folding motions allow generic vertex geometries to have as many as five stable states. In special geometries with collinear folds and symmetry, more branches emerge leading to as many as six stable states. Tuning the fold energy param… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
281
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(284 citation statements)
references
References 29 publications
2
281
0
Order By: Relevance
“…3. For this study we considered a maximum of 2 16 designs per tessellation, randomly selected from the 2 F possibilities, so that for 11 of the tessellations (#4-5, #9-10, #16-17, #20-21, #23, #25, and #27) the results are not complete, but rather indicate a trend. Note that we expanded the number of possible designs by removing the polyhedra for which all faces have been made rigid from the extruded unit cell, as those would have resulted in rigid parts completely disconnected from the architected materials.…”
Section: Enhancing the Reconfigurabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…3. For this study we considered a maximum of 2 16 designs per tessellation, randomly selected from the 2 F possibilities, so that for 11 of the tessellations (#4-5, #9-10, #16-17, #20-21, #23, #25, and #27) the results are not complete, but rather indicate a trend. Note that we expanded the number of possible designs by removing the polyhedra for which all faces have been made rigid from the extruded unit cell, as those would have resulted in rigid parts completely disconnected from the architected materials.…”
Section: Enhancing the Reconfigurabilitymentioning
confidence: 99%
“…While most of the proposed origami-inspired metamaterials are based on 2D folding patterns, such as the miura-ori, [11][12][13][14][15][16][17] the square twist 18 and the box-pleat tiling, 19 it has been shown that cellular structures can be designed by stacking these folded layers, 13 or assembling them in tubes. [20][21][22][23] Furthermore, by taking inspiration from snapology 24,25 -a modular origami technique -a highly reconfigurable 3D metamaterial assembled from extruded cubes has been designed.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of this coupling are seen in both naturally occurring scenarios, such as intestinal villi and pollen grains (4,5), and find use in man-made structures such as programmable metamaterials (6)(7)(8)(9). When these shells have multistable configurations, the transition between them is opposed by geometrically enhanced rigidity resulting from the dominant stretching energy.…”
mentioning
confidence: 99%
“…Various multi-stability mechanisms in origami-based systems were explored previously [25][26][27][28][29][30], but the pressure-dependent multi-stability discussed in this research is uniquely different in several aspects. It originates from the combination of two different physical principles: origami elastically induced and fluidic pressure induced multi-stability.…”
Section: Introductionmentioning
confidence: 99%